Assessing the impact of information, education and communication activities regarding menstrual hygiene practices among adolescent girls 13-17 years in the rural area of Amritsar - Jyoti, Kamal; Lal, Mohan; Mahajan, Sanjeev; Singh, Tejbir (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescence period (10-19 years) is a transitional stage. Adolescents constitute 20% of the total population in India. Menarche marks the beginning of a multitude of physical, physiological, and psychological changes in the lives of the girls. During menstruation, hygiene-related practices are of considerable importance because lack of knowledge and poor menstrual hygiene practices makes them prone to reproductive tract infections. Methods: The study was carried out among 13-17 years adolescent girls studying in the Government Senior Secondary Schools at Nagkalan and Sohian Kalan and out of school adolescent girls of the same age group who were residents of these two villages. Base line information was collected from eligible girls and then IEC activities were conducted on menstrual hygiene practices. After three months the impact of IEC activities was assessed and valid conclusions were drawn. Results: 81.13% have attained menarche. 40.6% were using both sanitary pads and cloth, only 7.4% were using only cloth as menstrual absorbent. Almost 3/4th (72.27%) respondents used dumping into open space and pond as method of disposal for used absorbent and after intervention this percentage was decreased to 44.9%. Conclusions: After IEC activities a greater number of adolescent girls were aware regarding safe menstrual hygiene practices.